Forage Sorghum Silage Cost-Return Budget in South Central Kansas - Ibendahl, Gregg; Shoup, Douglas; O'Brien, Daniel M. (My University, 2015)
The cost-return projection estimates the cost of producing forage sorghum silage in south central Kansas.
MF648_2015_04
Keywords: MF648; Economics; Crops; MF